Assessment of Salivary MMP-8 and IL-1β for the Diagnosis of Periodontal Diseases in Pakistani Population - Kainat, Rida; Ahmed, Iftikhar; Alolaywi, Abdullah Mohammed; Waheed, Humera; Sultan, Zohaib Khurshid; Moin, Syed Faraz (European Journal of Dentistry, 2023)
Objective Clinical methods use the subjective diagnosis of periodontal diseases by visual observation that could result in differences and variability of diagnosis. The addition of specific markers could aid in the accurate diagnosis of the local population. The objective of the study was to target two of the major proteins for possible significance in such an approach.Materials and Methods Unstimulated saliva samples were collected from 60 participants aged between 18 and 70 years. Three groups each with twenty participants were recruited into periodontitis, gingivitis, and healthy control.Statistical Analysis The samples were analyzed using human enzyme-linked immunosorbent assay kits for matrix metalloproteinase-8 (MMP-8) and interleukin-1β (IL-1β).Results SPSS version 20 was used to analyze the result. Posthoc analysis by Tukey's test revealed that MMP-8 levels were higher in gingivitis and periodontitis groups as compared with healthy controls. The test also revealed that IL-1β levels were higher in the periodontitis group compared with the healthy control and gingivitis group. Additionally, one-way analysis of variance analysis showed a significant effect on probing depth in gingivitis and periodontitis patients. The mean age of periodontitis group was significantly higher than other groups.Conclusion Salivary biomarkers may provide useful diagnostic information and could be utilized as tests for periodontal disease screening, prognosis, and prediction.
Keywords: saliva; biomarkers; MMP-8; IL-1β; gingivitis; periodontal disease